Penerapan Teori Penetrasi Sosial dalam Komunikasi Virtual (Studi Kasus pada Komunitas Penggemar BTS atau ARMY) - Budiono, Bagus (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The fan community, particularly in Korean music culture, commonly referred to as K-Pop, is flourishing in tandem with the evolving times. Beyond being a platform for sharing common interests, fan communities have become a means for interaction, discussion, and the formation of friendships. The progression of time, facilitated by digital technology, further supports this through the creation of fan communities engaging in virtual interactions, predominantly on social media platforms. The objective of this research is to explore the dynamics of virtual communication relationships within the BTS fan community (ARMY) using the Social Penetration Theory. This theory is employed to comprehend the process of interpersonal relationship development within virtual communities. The research adopts a qualitative research method with a case study approach, utilizing in-depth interviews and observations as data collection techniques. The study involves 15 active members of the BTS fan community who interact on social media fanbase platforms. The research findings shed light on the understanding of how BTS fan community members establish and foster a sense of intimacy through virtual communication, exploring the application, influencing factors, and stages of these relationships. The theoretical and practical implications of this research, supported by previous studies, can provide guidance for community managers and other researchers, contributing to the development of the Social Penetration Theory in the context of virtual communication.